KORELASI KOMPONEN KEBUGARAN JASMANI DENGAN PRESTASI BELAJAR PADA SISWA SD NEGERI 2 CIKERUH - Nurul Uyun; Reni Farenia; Trisnasari Hafsah (JURNAL ILMU FAAL OLAHRAGA INDONESIA, 2020)
Physical fitness is a measure of health status as a basic physical condition of someone to perform daily activity. In this study, measurement pf physical fitness component consisted of cardiorespiratory endurance, body composition, muscular flexibility, and muscular strength. The purpose of this study is to know whether there is correlation between physical fitness and academic achievement. This study used observational analytical method with cross-sectional design. Data were collected by total sampling method, and there were eighty-two students from Cikeruh 2 Elementary School in Jatinangor from 4th, 5th, and 6th grade. Physical fitness assessment in this study consisted of step test, body mass index (BMI), push-up, and sit-up. Academic achievement data was collected from final examination result. Most students (74,49%) has enough physical fitness. There is no significant correlation between physical fitness and academic achievement. Thus, based on this study, it was expected to conduct further study about other factors which affects the academic achievement.